AG Enterprise "Yummy Toaster" / Nur Ahsikin Fazira Yusof - Yusof, Nur Ahsikin Fazira (2020)
Our company provides people with a multifunctional toaster called Yummy Toaster especially for those who often have limiting factor to prepare for breakfast and always skipping their breakfast. Yummy Toaster can toast and put the jam on the bread according to the user demand. It can save time and energy also safe to be use anytime. It used stainless steel material that can make it last longer also have some features that will make people life easier. The design and style of our product is unique. We offer superior quality and design at affordable prices. Our products, design and finishes will continue evolve based on consumer trends and demands